Strategi Komunikasi Guru Dalam Meningkatkan Efektifitas Pembelajaran - Arifia Retna Yunita (CV. Alim's Publishing, 2024)
Abstract The role of teacher comunication is very important in the learning process, with technology tahers are required to be able to integrate technology in distance learning but also implement teacher communication strategies as the biggest connector in the effectiveness of distance learning. The way to facilitate good communicationis using a procedure from attention to action procedure. With five steps abbreviated as AIDDA. A is attention, I is interest, D is desire, D is decision, and A is action. The method used in this research is descriptive phenomena or data findings in the field as they are. This research was contuted by MA Zainul Bahar Wringin Bondowoso. Results of interviews that there are difficulties in convincing parents so that students are not asked to help work and provide motivation to study in group. The above requires a communicationstrategy with parents and childrenso that they can still carry out their duties as students and accept their rights as students by getting materials and teachers.